ChemInform Abstract: Flexible Access to Conformationally‐Locked Bicyclic Morpholines. Issue 5 (4th February 2014) - Bogacki, Rachael; Gill, Duncan M.; Kerr, William J.; Lamont, Scott; Parkinson, John A.; Paterson, Laura C.
Abstract This describes the synthesis of several examples of the title motif, e.